2010
DOI: 10.1177/145749691009900407
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Rupture of Abdominal Aortic Aneurysm

Abstract: All patients with rAAA had been seen by a GP or cardiologist within a year prior to presentation. The cost effectiveness of selective AAA screening should be evaluated in a larger study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In line with this, one retrospective study has shown that patients with formerly unknown and emergently operated on AAAs (treated for symptoms or rupture) have high prevalence (45%) of previously diagnosed CHD. 8 The foremost considerations in treating CHD patients are the possibly increased risk of perioperative complications and diminishing benefits in survival despite successful operative treatment. However, in elective repair of AAA, CHD (stable disease or previous acute coronary syndrome) does not influence perioperative mortality, 22 and prior MI and stable CHD are only minor factors in considering 5-year mortality after elective repair of AAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, one retrospective study has shown that patients with formerly unknown and emergently operated on AAAs (treated for symptoms or rupture) have high prevalence (45%) of previously diagnosed CHD. 8 The foremost considerations in treating CHD patients are the possibly increased risk of perioperative complications and diminishing benefits in survival despite successful operative treatment. However, in elective repair of AAA, CHD (stable disease or previous acute coronary syndrome) does not influence perioperative mortality, 22 and prior MI and stable CHD are only minor factors in considering 5-year mortality after elective repair of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…7 In fact, a large proportion of patients treated emergently for AAA have CAD. 8 Currently, a small number of individual studies with heterogeneous study settings have reported exclusively the prevalence of AAA among patients with angiography-verified CAD. [9][10][11][12][13][14] Preliminary evidence also suggests that the severity of CAD is associated with prevalence of AAA.…”
mentioning
confidence: 99%
“…A Swiss study showed that among 213 consecutive rAAAs emergently operated on between 1998 and 2005, all patients had been seen by their general practitioner or a cardiologist within a year before the presentation. Therefore, they may have benefited from AAA screening [20].…”
Section: Abdominal Aortic Aneurysm (Aaa)mentioning
confidence: 99%
“…Coexistence of other vascular diseases with AAA has been well-established, and increased prevalence of AAA in population with peripheral artery disease (PAD) and coronary artery disease (CAD) has been proven in multiple studies (21)(22)(23)(24)(25). Cerebrovascular disease (CVD) is considered to share the common etiology and pathogenesis with other major vascular diseases (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%